Endourological Management of Urinary Tract Strictures: A Systematic Review of Efficacy, Safety, and Durability across the Ureter and Urethra - Regenio Akira Handoyo; Ilham Saptia Nugraha (International Medical Journal Corp. Ltd, 2026)
Introduction Urinary tract strictures, a constellation of fibrotic conditions encompassing urethral stricture disease (USD) and benign ureteral strictures (US), impose significant morbidity due to the aggressive nature of recurrence after traditional mechanical endoscopic management (Yeow et al., 2024; Malkhasyan et al., 2013). While open surgical reconstruction remains the established gold standard for complex lesions, endourological methods are frequently attempted as the initial management strategy, especially for shorter strictures or patients with multiple comorbidities (Stein et al., 2001; Buckley et al., 2014). This systematic review provides an integrated, in-depth synthesis of recent, high-certainty evidence concerning the long-term efficacy, functional outcomes, and safety profiles of advanced endourological modalities, specifically focusing on Drug-Coated Balloons (DCB) for the urethra and precise laser-assisted endoureterotomy for the ureter (DeLong et al., 2025; Gökçe et al., 2022). Methods A rigorous systematic literature search, adhering strictly to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, was performed across major biomedical databases, targeting studies published between 1998 and 2025 (Page et al., 2021). Inclusion criteria required studies to report comparative outcomes or long-term follow-up (minimum 12 months) of procedures such as dilation, direct vision internal urethrotomy (DVIU), DCB, balloon ureteroplasty, and endoureterotomy (Patel et al., 2024). A highly selected cohort of at least fifteen high-quality clinical studies, including pivotal randomized controlled trials (RCTs) and prospective cohorts, were included for detailed quantitative synthesis (Patel et al., 2024). Methodological quality was assessed using the Cochrane Risk of Bias 2.0 tool for RCTs and the Newcastle-Ottawa Scale for non-randomized studies (Higgins et al., 2011). A total of eleven distinct clinical and mechanistic outcomes were quantified, including the five-year Freedom from Re-intervention (FFR), Maximum Urinary Flow Rate (Qmax), International Prostate Symptom Score (IPSS), and the histological quality of wound healing (DeLong et al., 2025; Gökçe et al., 2022). Results The combined analysis across the urinary tract demonstrated a significant clinical superiority of modern, adjunct-enhanced endourology (DeLong et al., 2025). Traditional mechanical management (dilation or DVIU) of anterior urethral strictures yields long-term recurrence rates ranging from 60% to 80%, confirming the inherent limitation of purely physical treatment against spongiofibrosis (Patel et al., 2024; Yu et al., 2024). In sharp contrast, the application of the paclitaxel-eluting DCB in recurrent bulbar USD (≤ 2 cm) demonstrated remarkable long-term durability, achieving an estimated FFR of 71.7% at five years in the ROBUST I trial (DeLong et al., 2025). This sustained success was functionally confirmed, with mean Qmax increasing from a severely obstructed 5.0 mL/s at baseline to 19.9 mL/s at the five-year follow-up, alongside a profound reduction in mean IPSS from 25.2 to 7.2 (DeLong et al., 2025). For ureteral strictures, combination techniques, such as balloon dilation coupled with endoureterotomy for lower ureteral strictures, achieved high success rates of 86.67% at one year (Diao et al., 2023). Preclinical data further indicated that Ho:YAG laser endoureterotomy yields superior histological remodeling and a reduced fibrotic response compared to mechanical balloon dilation alone (Gökçe et al., 2022). Discussion The synthesized data compels a major revision of clinical algorithms, strongly endorsing the deployment of DCB as a validated, durable, minimally invasive option for selected recurrent bulbar urethral strictures, effectively interrupting the pathological cycle of injury and re-scarring (Yeow et al., 2024). In the ureter, optimal outcomes rely heavily on technical refinement—specifically, utilizing precise laser incision and careful patient selection, emphasizing that shorter stricture length is the primary predictor of endourological success in both tracts (Gökçe et al., 2022; Heyns et al., 1998). The high complication risks observed in vulnerable cohorts, notably kidney transplant patients managed endourologically, further stress the need for conservative selection criteria, often favoring upfront open reconstruction for complex lesions (Wang et al., 2024). Conclusion Durable endourological success across the urinary tract is contingent upon the meticulous selection of patients and the strategic integration of modern, biologically or technically enhanced technologies (Buckley et al., 2014). The DCB is established as a highly effective, sustained treatment for recurrent short bulbar USD, offering objective and subjective relief comparable to long-term open reconstruction outcomes (DeLong et al., 2025; Stein et al., 2001). For ureteral strictures, precise laser endoureterotomy combined with optimal stenting offers the best endoscopic outcomes by promoting favorable tissue remodeling (Gökçe et al., 2022). Future research must prioritize validating DCB use in longer, complex urethral strictures and conducting definitive RCTs to confirm the long-term clinical superiority of Ho:YAG laser endoureterotomy in human ureteral stricture management (Ricketts et al., 2024; Gökçe et al., 2022).